2015
DOI: 10.1016/j.apjtm.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of multidrug-resistance in Acinetobacter baumannii and dissemination of carbapenemase-encoding genes blaOXA-23-like, blaOXA-24-like and blaNDM-1 in Algiers hospitals

Abstract: This study highlighted the high prevalence of imipenem resistance in Acinetobacter baumannii in Algiers hospitals mediated mainly by blaOXA-23-like, blaOXA-24-like, and blaNDM-1 genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 55 publications
(113 reference statements)
11
24
0
Order By: Relevance
“…Previous studies have reported similar results (Jeannot et al, 2014;Santimaleeworagun et al, 2014;Khorsi et al, 2015;Mathlouthi et al, 2015;Memish et al, 2015;Wang et al, 2015). Khorsi et al (2015) analyzed the prevalence of A. baumannii multidrugresistance in hospitals in Algiers, and found that carbapenem resistance was mainly mediated by blaOXA-23 and blaOXA-24 genes. Wang et al (2015) also identified the blaOXA-23 gene in multidrug-resistant A. baumannii isolates from Libyan hospitals.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have reported similar results (Jeannot et al, 2014;Santimaleeworagun et al, 2014;Khorsi et al, 2015;Mathlouthi et al, 2015;Memish et al, 2015;Wang et al, 2015). Khorsi et al (2015) analyzed the prevalence of A. baumannii multidrugresistance in hospitals in Algiers, and found that carbapenem resistance was mainly mediated by blaOXA-23 and blaOXA-24 genes. Wang et al (2015) also identified the blaOXA-23 gene in multidrug-resistant A. baumannii isolates from Libyan hospitals.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, 41.7% of gram-negative bacteria, including A. baumannii, were MDR strains and 60% were positive simultaneously for metalo beta lactamase and AmpC production. Mahdian from Tehran and Khadidja from Aljazira reported that 70.3% and 93.6% of isolated A. baumannii from clinical specimens were found to be MDR strains (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are of low frequency, and most of the studies have been conducted on the bacteria of the Enterobacteriaceae family. Studies performed to identify the qnr genes in A. baumannii isolates have not been so successful (15). Another important mechanism in the creation of quinolones resistance is mutation in quinolone resistance-determining regions (QRDR), where the target enzymes of DNA gyrase (gyrA) and Topoisomerase IV (parC) are affected.…”
Section: Introductionmentioning
confidence: 99%